1971
DOI: 10.1139/y71-001
|View full text |Cite
|
Sign up to set email alerts
|

The Action of Carnitines on Cortical Neurons

Abstract: Compounds related to carnitine have been applied iontophoretically from five-barrelled micropipettes to neurons of the cerebral cortex of anesthetized cats. Both optically active and racemic mixtures of carnitine, acetyl carnitine, carnitine nitrile, and acetylcarnitylcholine had an excitatory action on cells excited by acetylcholine. The levorotatory forms were generally, but not invariably, stronger excitants than their enantiomers. Atropine administered intravenously blocked the action of all carnitines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

1980
1980
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…Besides, we have tested carnitine for stereospecificity; the L-form was found to increase spontaneous firing, while the D-compound was almost inactive. This is in agreement with the results of other authors, who employed the microiontophoretic technique (Falchetto et al, 1971), or biochemical methods (Strack and Thomitzek et al, 1966). All of them concluded that the effects displayed by carnitine and derivatives could be selectively attributed to the Lforms.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Besides, we have tested carnitine for stereospecificity; the L-form was found to increase spontaneous firing, while the D-compound was almost inactive. This is in agreement with the results of other authors, who employed the microiontophoretic technique (Falchetto et al, 1971), or biochemical methods (Strack and Thomitzek et al, 1966). All of them concluded that the effects displayed by carnitine and derivatives could be selectively attributed to the Lforms.…”
Section: Discussionsupporting
confidence: 93%
“…Falchetto et al (1971) found a slow rate of onset of excitation in cortical neurons. Tempesta et al (1982Tempesta et al ( , 1985 observed long latency of most neuronal responses to D, L-and L-acetylcarnitine in the rat brainstem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ALC increases acetylcholine synthesis and also has cholinomimetic activity [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Its stereochemical similarity with acetylcholine (Falchetto et al, 1971) suggests its possible cholinergic activity and use in a pharmacologic study of senile cognitive decline.…”
Section: Introductionmentioning
confidence: 99%